O ocaso da noção de combinatória do Tractatus - Avendano, Diego de Souza (2016)
The aim of this dissertation is outline the course by which the concept of rule "arises" in Wittgenstein's thought. I shall consider that the origin of the approach to the concept of "rule" lies in the rapid development of the author's thinking between 1929-1934. His immediate problem was to remedy the glaring error, presented by Ramsey, on the Tractarian remarks about the logical necessity. In order to correct this error, Wittgenstein introduces two major innovations with which he believes that can solve the problem and still preserve the rigid tractarian demarcation between logical truth and empirical truth. First, he will replace the combinatorial model underlying the natural language that prevailed in the Tractatus by a conception which he describes as a system of propositions (Satzsysteme), in which language would be considered as a complex system of autonomous propositional calculi. This change make possible preserves the thesis that all necessity is a logical necessity, however, it will be necessary to abandon the referential conception of meaning and the logical independence of elementary propositions. Thus, our proposal in this dissertation is to establish all aspects of the Tractarian philosophy that precede and sustain the proposal of language as correspondence, emphasizing that the abandonment shall result in changes such as: 1) a word has its meaning only in the context of its propositional system; 2) the meaning of any word is the totality of the rules governing its use in this system; 3) The meaning of a proposition is the method of its verification. Finally, in order to understand the context of these changes, it seems to be the case, that in one hand, we need to establish the essence and general form of the proposition in the Tractatus, and thereby elucidate some aspects of what are the essential traits of language and the world; On the other, to establish the limits and the scope of analysis, so we can understand its mutation outlined in accordance with the new criterion of sense – the rules – since what counts as the object of analysis will not be determined by a general form, but displayed by a “possible calculus”.